Minimum energy trajectory planning method for robot manipulator mounted on flexible base - Abe, Akira (2013 9th Asian Control Conference (ASCC), 2013)
This paper proposes a minimum energy trajectory planning method with residual vibration reduction for a robot manipulator mounted on flexible base, in which a point-to-point motion task of the manipulator is considered. In the proposed method, the joint angle of the robot manipulator is generated by radial basis function networks (RBFNs). The maximum residual vibration amplitude and operating energy are adopted as the objective functions, and then, the RBFNs are tuned by an elitist non-dominated sorting genetic algorithm (NSGA-II). The trajectory obtained using the proposed method can suppress the residual vibration of the flexible base in energy conservation. Results obtained from simulations reveal a trade-off relationship between the residual vibration amplitude and the operating energy. Furthermore, the validity of the proposed method is confirmed experimentally.